The drop plate method as an alternative for Azospirillum spp. viable cell enumeration within the consensus protocol of the REDCAI network = La técnica de la microgota como alternativa para el recuento de Azospirillum spp. dentro del protocolo de la Red de Control de Calidad de Inoculantes (REDCAI) - Di Salvo, Luciana P.; Garcia, Julia Elena; Puente, Mariana Laura; Amigo, Josefina; Anríquez, Analía; Barlocco, Claudia; Benintende, Silvia; Bochatay, Tatiana; Bortolato, Marta; Cassán, Fabricio; Castaño, Carolina; Catafesta, Melina; et al. (Asociación Argentina de Microbiología, 2025)
Quality evaluation of commercial inoculants is essential to warrant an adequate crop response to inoculation within a biosecurity framework. In this sense, this work is aimed at standardizing and validating the drop plate method for the enumeration of Azospirillum viable cells as an alternative to the spread plate technique, which is currently proposed in the consensus protocol of the REDCAI network. Between 14 and 25 private and public laboratories participated in three independent trials. We obtained consistent and robust results that allowed to confirm that both techniques are equivalent, concluding that the drop plate method is an alternative enumeration technique that is adequate to be included in the abovementioned consensus protocol.